Early diagnosis and appropriate management of vaginal leiomyoma in rural areas - Nizomy, Ihya Ridlo; Budinurdjaja, Pribakti; Armanza, Ferry; Yuseran, Hariadi; Joyce; Lahdimawan, Inas Tsurayya Fauziah (Universitas Airlangga, 2024)
HIGHLIGHTS Extrauterine leiomyoma, including vaginal leiomyoma, is an exceedingly rare condition with complex pathogenesis and management. Clinical evaluation and high-quality imaging are required to confirm the diagnosis of vaginal tumor. If there are insufficient facilities, referrals must be made. Operative management using vaginal approach was described for treating vaginal leiomyoma. ABSTRACT Objective: To describe the challenges of early diagnosis and appropriate management of vaginal leiomyoma in rural areas. Case Report: A 26-year-old woman, P1A0, was referred from a rural hospital and presented a chief complaint of vaginal mass. The patient was admitted to the tertiary hospital with suspected malignant vaginal tumor and underwent a biopsy, which revealed leiomyoma on pathological examination. Despite conservative treatment, the mass continued to grow, unaffected by the menstrual cycle, causing discomfort. Following a second hospital admission, the patient underwent surgical management of extirpation and vaginal reconstruction. The microscopic finding of the tumor showed myositis cell proliferation with hyperplastic growth, monotonous nuclei, and variable cell shapes, supporting the diagnosis of vaginal leiomyoma. During postoperative monitoring, there was no vaginal bleeding. Thereafter, on the day following surgery, it was found that the right labium major was swollen. This was treated with anticoagulants, topical NSAIDs, and a sitz bath. The patient was discharged from the hospital in good condition and had an uneventful postoperative recovery. Conclusion: Although the incidence of vaginal leiomyoma is uncommon, precise early diagnosis and appropriate management might improve outcomes, particularly in rural areas.